Environmental, Social and Governance (ESG) and Investment Decision in Bangladesh - Sultana, Sayema; Zulkifli, Norhayah; Zainal, Dalilawati (MDPI, 2018)
As a key facet of sustainable development, environmental, social and governance (ESG) discretion on stock market investment decision is gaining prevalence following the global financial crisis. ESG considers the sustainable return, risk reduction, and accountability aspects of investments. This study is an exploration of the individual stock market investors' preferences for ESG issues and the influence that purpose of investment has on investment decision-making, by testing the investment horizon as a moderator. The theoretical background was taken from the theory of planned behavior (TPB), goal setting theory (GST), and the behavioral asset pricing model (BAPM). The study uses the sequential mix method of research, starting with an interview followed by a survey, which was conducted among individual stock market investors in Bangladesh, using simple random sampling. Structural equation modeling (SEM) analysis was carried out using Warp PLS version 6.0. The key findings of this study delineate the effect of ESG issues and the purpose of investment on investment decision-making. The contribution of the study signifies the moderating role of the investment horizon, which confirms the importance of the long-term horizon as a time and risk diversification factor. The sparse utilization of the United Nations Global Compact (UNGC) (2004) and Thomson Reuters Corporate Responsibility Index (TRCRI) (2013) as measurement scales in this study is mentioned. This study has made practical contributions for managers, investors, and regulators.